Association of clinicopathological characteristics with secondary neoplastic lymphoproliferative disorders in patients with lymphomatoid papulosis. - Nikolaou, Vassiliki; Papadavid, Evangelia; Ekonomidi, Afroditi; Dalamaga, Maria; Marinos, Leonidas; Stratigos, Alexandros; Papadaki, Theodora; Antoniou, Christina (Leuk Lymphoma, 2015)
Lymphomatoid papulosis (LyP) refers to an indolent cutaneous lymphoma. The association of prognostic clinicopathological risk factors with a second hematologic malignancy has not yet been determined. We investigated the prognostic effect of clinicopathological characteristics on the occurrence of a second lymphoma, as well as the first-line treatment, in 24 patients diagnosed with LyP using logistic regression models. We showed that lymphoma occurrence was associated with a lower mean age at onset of LyP symptoms, histological types B and C, head-located LyP lesions and a higher frequency of LyP recurrences. In multivariate analyses, histologic type A was associated with a lower risk of second lymphoma (odds ratio [OR] = 0.12, 95% confidence interval [CI] 0.014-0.98; p = 0.045) adjusting for age of LyP first symptomatology, and an important increased lymphoma-free survival rate (long-rank test; p = 0.06). Clinicopathological characteristics are important in defining the clearance or persistence of LyP lesions and may predict the occurrence of a second lymphoma.
Keywords: Adult; Aged; Female; Follow-Up Studies; Humans; Kaplan-Meier Estimate; Lymphomatoid Papulosis; Lymphoproliferative Disorders; Male; Middle Aged; Neoplasms, Second Primary; Odds Ratio; Recurrence; Skin Neoplasms; Time Factors; Young Adult